A 12-GHz high output power amplifier using 0.18µm SiGe BiCMOS for low power applications - Kumar, Thangarasu Bharatha (2013)
This paper presents a fixed gain high output power amplifier with performance determined by using on-wafer measurement. The amplifier is fully differential based on inductive load and resistive degeneration which is designed using a 0.18 μm SiGe BiCMOS process. The amplifier achieves power gain of 7.2 dB, 3-dB bandwidth of 2.06 GHz, operating frequency of 12 GHz, power consumption of 12 mW using 1.8 V supply voltage and the input referred 1-dB gain compression point of -1.6 dBm. The designed amplifier occupies a die area of 380 μm × 340 μm.